1983
DOI: 10.2172/6626681
|View full text |Cite
|
Sign up to set email alerts
|

Geothermal assessment of a portion of the Escalante Valley, Utah

Abstract: This book was prepared as an account of work sponsored by an agency of the Unfted States Government. Neither the United States Government nor any agency thereof, nor any of their employees. makes any warranty, express or implied, w assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product or process disclosed, or represents that its use would not infringe privately owned rights. References herein to any specific commercial product, proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Samples 33, 34, and 39 have high TDS values ranging from l,592 to 1,646 ppm and are enriched in N a, Ca, SO 4' and Cl as compared to other Escalante Valley samples exclusive of thermal areas. Klauk and Gourley (1983) report that Li versus B plots for these samples were similiar to Li/ B plots for Thermo Hot Springs samples, suggesting a geothermal anomaly in the area north of Zarie. They applied the mixing model of Truesdell and Fournier (1977) to sample 33 and derived a temperature of 128°C, which is reasonable because the Na-K-Ca temperature of 103°C is probably low due to mixing.…”
Section: Percent Of Total Milliequivalents Per Liter C I -Anionsmentioning
confidence: 74%
See 2 more Smart Citations
“…Samples 33, 34, and 39 have high TDS values ranging from l,592 to 1,646 ppm and are enriched in N a, Ca, SO 4' and Cl as compared to other Escalante Valley samples exclusive of thermal areas. Klauk and Gourley (1983) report that Li versus B plots for these samples were similiar to Li/ B plots for Thermo Hot Springs samples, suggesting a geothermal anomaly in the area north of Zarie. They applied the mixing model of Truesdell and Fournier (1977) to sample 33 and derived a temperature of 128°C, which is reasonable because the Na-K-Ca temperature of 103°C is probably low due to mixing.…”
Section: Percent Of Total Milliequivalents Per Liter C I -Anionsmentioning
confidence: 74%
“…Sample 1, about 15 km northwest of samples 33, 34, and 39, has an even higher TDS value (2,486 ppm) due largely to Cl content. Other chemical parameters and geothermometer temperatures (table 2) are similiar for the four samples, thus increasing the size of the geothermal anomaly described by Klauk and Gourley (1983).…”
Section: Percent Of Total Milliequivalents Per Liter C I -Anionsmentioning
confidence: 89%
See 1 more Smart Citation
“…The valley is filled with more than 300 m (1,000 ft) of alluvial, colluvial, fluvial, lacustrine, and aeolian unconsolidated and semi-consolidated deposits (Klauk and Gourley, 1983, p.3). Klauk and Gourley (1983, The valley is situated between two major, roughly east-west trending mineral (or igneous) belts. The Pioche-Mqsvale mineral belt (26 Ma) lies to the north, and the Delamar-Iron Springs mineral belt (20 Ma) lies to the south (Rowley and others, 1979).…”
Section: Mourvtains Comrad0mentioning
confidence: 99%
“…Only a small p a r t o f t h i s information i s p e r t i n e n t t o t h e hydrology and geothermal occurrences o f north-central Box Elder County, Utah. i n v e s t i g a t i o n s such as those by Klauk and Gourley (1983), Struhsacker e t al., (1983), Glenn e t al., (19801, deVries (19'821, and Mariner and Willey (1976) Analogous were h e l p f u l i n e s t a b l i s h i n g presentation methods and data i n t e r p r e t a t i o n . Mundorff (1970) published a study on most o f the major thermal springs i n He found t h a t waters i n northwestern Utah generally had low Heylmun (1966) and Goode (1978) might be underlain with hot, s a l i n e water, and t h a t the geothermal gradient f o r t h i s area may be abnormally high.…”
Section: Previous Workmentioning
confidence: 99%